2017
DOI: 10.3390/ijerph14030253
|View full text |Cite
|
Sign up to set email alerts
|

Risk Estimates and Risk Factors Related to Psychiatric Inpatient Suicide—An Overview

Abstract: People with mental illness have an increased risk of suicide. The aim of this paper is to provide an overview of suicide risk estimates among psychiatric inpatients based on the body of evidence found in scientific peer-reviewed literature; primarily focusing on the relative risks, rates, time trends, and socio-demographic and clinical risk factors of suicide in psychiatric inpatients. Psychiatric inpatients have a very high risk of suicide relative to the background population, but it remains challenging for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 64 publications
(111 reference statements)
2
47
2
1
Order By: Relevance
“…The suicide risk is increased in patients with depression . In our study, the number of attempts and completed suicides was low and was not increased in patients with LE compared with the general population.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The suicide risk is increased in patients with depression . In our study, the number of attempts and completed suicides was low and was not increased in patients with LE compared with the general population.…”
Section: Discussioncontrasting
confidence: 54%
“…26 The suicide risk is increased in patients with depression. 6 In our study, the number of attempts and completed suicides was low and was not increased in patients with LE compared with the general population. Previous studies have described that suicidal ideation is common in patients with SLE and that the IRs of completed suicides and attempts are also increased.…”
Section: Discussionmentioning
confidence: 40%
“…Among females, the rates per 100,000 of the population increased for those aged: (35-44) by 37% (3.5 to 4.8), (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) reported that approximately 40% had some previous contact with the mental health services (Kielty et al, 2014). While rates of suicide in psychiatric hospitals vary across international studies, it is estimated that approximately 5% of all suicides occur among currently admitted service users (Madsen, Erlangsen, & Nordentoft, 2017;Walsh, Sara, Ryan, & Large, 2015). Suicide is one of five key A common approach in suicide prevention strategies and underpinned by WHO (2014) guidance is the importance of evidencebased interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the increase of suicide rate in females could be hypothesized to be caused by this population being more severely affected by the stress of being admitted to/discharged from inpatient psychiatric care [25]. Furthermore, affective disorders, frequently associated with increased incidence of completed suicide, show higher rates of prevalence in females than in males, potentially contributing to an increased ratio of completed suicide in females currently receiving inpatient psychiatric care, when compared to the suicide rate of the total population [20,26,27].…”
Section: Discussionmentioning
confidence: 99%